Childhood Cancer Survivorship Care in Limited Resource Settings: A Narrative Review and Strategies to Promote Global Health Equity - David H. Noyd; Ana Carolina Izurieta-Pacheco; Rizine Mzikamanda; Nana Nakiddu; Dao Thi Thanh An; Bounpalisone Souvanlasy; Ritu Bhalla; Chandan Kumar; Poonam Bagai; Remziye Semerci; Tuba Arpaci; Kristin Schroeder; et al. (JCO Global Oncology)
The WHO Global Initiative for Childhood Cancer, prompted by the marked inequity of survival across the globe, aims to increase survival rates in low- and middle-income countries to 60% by 2030. In tandem with this effort, implementing survivorship-focused care is crucial to mitigate late effects and prevent early mortality beyond the 5-year survival end point. The observed burden of secondary malignancies, cardiovascular disease, and other chronic health conditions in adult survivors of childhood cancer in high-income countries provides guidance to generate evidence in limited-resource settings. The implementation of risk stratification tools, population health management, and development of contextually relevant health care delivery models, within the current landscape of survivorship care in Latin America, Africa, and Asia as examples, are vital to continue the momentum to ensure equitable care and quality of life for all survivors of childhood cancer. This narrative review informed by expert opinion serves as a call to action for survivors, advocacy groups, health professionals, health systems, governments, and global organizations to look beyond the 5-year survival benchmark.